2011
DOI: 10.1308/147870811x13137608455055
|View full text |Cite
|
Sign up to set email alerts
|

Trends in presentation of bone and soft tissue sarcomas over 25 years: little evidence of earlier diagnosis

Abstract: Earlier diagnosis is a key aim in achieving improved outcomes for patients with cancer. Bone and soft tissue sarcomas represent approximately 1% of all malignant tumours. Delays in diagnosis are frequent both because of their rarity and because the clinical features are easily confused with other conditions. In 2000 advice on earlier diagnosis was widely publicised. This study investigates how two factors that may act as a proxy for delay in diagnosis have varied over a 25-year period and whether there is evid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 17 publications
3
37
1
2
Order By: Relevance
“…This factor can cause difficulties in detection since a STS lying deep has hardly any symptoms. 6,11 The results of our dataset match with this observation as the majority of malignancies were situated deep while benign lesions were more likely to be located subcutaneously.…”
Section: Depthsupporting
confidence: 83%
See 2 more Smart Citations
“…This factor can cause difficulties in detection since a STS lying deep has hardly any symptoms. 6,11 The results of our dataset match with this observation as the majority of malignancies were situated deep while benign lesions were more likely to be located subcutaneously.…”
Section: Depthsupporting
confidence: 83%
“…This is a little less than the usual size for STS at initial presentation over the past 25 years. 6 Nevertheless, while benign soft tissue tumours are approximately 5cm in size, sarcomas are most often clearly positive for the parameter 'size >5cm'. As size correlates directly with chances of survival for patients with STS, it is crucial to diagnose them at an early stage.…”
Section: Sizementioning
confidence: 99%
See 1 more Smart Citation
“…Diagnostic delay is thought to contribute to this. Sarcomas are diagnosed later in the UK patients, and are larger at the time of biopsy, even after new cancer referral guidelines from 2000 12. The time from first symptom to diagnosis in Ewing sarcoma is one of the longest of all paediatric tumours, with a median time of 3–6 months and case reports of tumours that were missed on imaging or pathology up to 3 years earlier 13–15…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have also found the presence of pain to be an unreliable indicator of malignancy. 10,20 Current guidelines for referral include size >5 cm, increasing in size, deep to fascia, painful and recurrence after previous excision. 11,12 We found STL depth to be a second-degree associate in our study.…”
Section: Discussionmentioning
confidence: 99%